45 Borderline ovarian tumors – 10 years single center experience. (18th September 2019) - Fernandes, R; Anton, C; Silva e Silva, A; Mancusi Carvalho, JP; Araújo, M; Dias Genta, ML; Sampaio, D; Miglino, G; Dias, A; Sadalla, JC; Paula Carvalho, J
Abstract : Objectives: To evaluate the prevalence, subtypes and features of borderline ovarian tumors accordingly to the 2014 World Health Classification in the Oncology Institute of the State of São Paulo - São Paulo Faculty of Medicine. Methods: A retrospective analysis of patients diagnosed with borderline ovarian tumors (BOTs) included in the database of the institute. From January 2006 to June 2017 a total of 209 patients were included in the database. All diagnosis were reviewed and confirmed by the pathology department. All patients were submitted to preoperative workup and multidisciplinary evaluation. Patients submitted to surgery elsewhere were evaluated and submitted to complimentary surgery if needed. Accordingly to their age and pregnancy desire, they were submitted to a radical or fertility sparing approach if feasable. Stage at presentation, borderline subtype, size of tumors, tumor markers, route of surgery, complete or fertility sparing approach were analyzed. Results: From 2006 to 2017, 209 patients presented with Borderline ovarian tumors. Stage I represented 94% of all cases, Stage II and III appeared with 5% and 11% respectively. Subtipes were serous in 55%, 37% mucinous and 6% seromucinous. Micropapillary variant was found in 13% of cases. Fertility sparing approach was performed in 12% of all patients. Mean follow up was 111weeks. Conclusions: Borderline ovarian tumors represent an isolated entity among ovarian tumors. The majority of patients present at early stage thus permitting a minimally invasive approach. Behavior and recurrence depends on the characteristics of each tumor and should be considered when planning a conservative or radical approach.